Residential Mobility and Youth Well-Being: Research, Policy, and Practice Issues. - Scanlon, Edward; Devine, Kevin (Journal of Sociology & Social Welfare, 2001)
Despite an extensive body of sociological work suggesting that residential mobility reduces child well-being, the subject of relocation has been largely overlooked in social work and social welfare literature. Recent social policies threaten to increase the incidence of moving among low-income families in the United States. This paper reviews theoretical and empirical literature in this area and finds evidence that residential mobility reduces children's academic functioning, and may negatively affect other aspects of child well-being. These effects are especially strong for poor children from single parent families, making this issue of particular relevance for social work. The authors suggest implications for future research, propose policies to increase residential stability, and provide directions for social work practice with mobile children. Reprinted by permission of the publisher.